Business Capital, Social Interaction, Level of Education and Land Area on Income of Seaweed Farmers in Binamu District, Jeneponto Regency - Putri Ramadhani; Tuty Supatminingsih; Nurdiana Nurdiana; Muhammad Dinar; Muhammad Hasan (Pinisi Journal of Entrepreneurship Review, 2023)
This research looks at how the independent factors of company capital, social contact, level of education, and land area affect the dependent variable of income of seaweed cultivators either directly or indirectly. The quantitative research methodology was used to conduct explanatory investigations. Seaweed cultivators became the research target group, and 30 respondents from Pabiringa Village in Binamu District, Jeneponto Regency, were selected using a saturated sampling methodology. The data was collected and processed using IBM SPSS 25 using multiple linear regression analysis and hypothesis testing after the respondents filled out the questionnaire. The research findings show that: (1) Working capital has a beneficial and significant effect on the income of seaweed cultivators; (2) Social interaction has a positive and significant effect on the income of seaweed farmers. (3) The level of education has no positive or significant effect on the income of seaweed cultivators. (4) Land area has a positive and significant effect on the income of seaweed farmers. (5) Business capital, social interaction, and level of education are all profitable and have a significant effect on the income of seaweed cultivators.